APPLICATION DELIVERY OF GOODS AND DOCUMENTS PT BYMATRANS USING VISUAL BASIC 6.0 - Ahmad Fauzi; Melani Dewi Lusita , S.Kom, MMSi (Jurnal Sistem Informasi, 2006)
This writing contains about administrative problems in delivery of documents orgoods at PT Bymatrans by using visual basic. The author proposes an application tofacilitate the process of shipping an item or docume nt. With the aim to make it easierto obtain information about the status of delivery of goods or documents.In this application can save the document or item of data, address, destination andlength of delivery.